Climate Change Effects on Secondary Compounds of Forest Trees in the Northern Hemisphere - Holopainen, Jarmo K.; Virjamo, Virpi; Ghimire, Rajendra P.; Blande, James D.; Julkunen-Tiitto, Riitta; Kivimäenpää, Minna (Frontiers in Plant Science, 2018)
Plant secondary compounds (PSCs) have high chemical and structural diversity and appear as non-volatile or volatile compounds. These compounds may have evolved to have specific physiological and ecological functions in the adaptation of plants to their growth environment. PSCs are produced by several metabolic pathways and many PSCs are specific for a few plant genera or families. In forest ecosystem, full-grown trees constitute the majority of plant biomass and are thus capable of producing significant amounts of PSCs. We summarize the literature and review recent progress in understanding the effects of known abiotic and biotic factors on PSC production of forest trees and PSC behaviour in forest ecosystems. The roles of different SM pathways under stress and their important role in protecting plants against abiotic and biotic factors are also discussed. There was evidence that major climate change factors, CO2 and warming, have contradictory effects on the main PSCs groups. CO2 increases phenolic compounds in foliage, but limit terpenoids in foliage and emissions. Warming decreases phenolic compounds in foliage, but increase terpenoids in foliage and emissions. Other abiotic stresses have more variable effects. PSCs may help trees to adapt to a changing climate and to pressure from current and invasive pests and pathogens. Indirect adaptation comes via the effects of PSCs on soil chemistry and nutrient cycling, the formation of cloud condensation nuclei from tree volatiles and by CO2 sequestration into PSCs in the wood of living and dead forest trees.